The Negative Regulator CXXC5: Making WNT Look a Little Less Dishevelled - Kim, Dongwon (J Invest Dermatol, 2017)
Wingless-related integration site (WNT)/β-catenin signaling regulates diverse physiological functions including tissue regeneration. Activation of WNT signaling can be inhibited by various agents. Lee et al. investigate the interaction of CXXC-type zinc finger protein 5 (CXXC5) with Dishevelled as one such negative regulator of WNT in hair follicle regeneration.